Some results on the logistic equation with harvesting - Montes de Oca, Francisco; Sarabia, José (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper considers the effects of harvesting on population model described by the Logistic Differential Equation. in no bisecant cases. Conditions for the existence of two bounded solutions onÂ R are glven.